Aspek Tata Kelola Perusahaan, Investment Opportunity Set dan Profitabilitas Pada Kualitas Laba di Perusahaan Indonesia - Rollis Ayu Ditasari; Sendy Dwi Haryanto; Muhamad Agus Sudrajat (Universitas PGRI Madiun, 2023)
This study aims to examine the effect of Share Ownership of Other Companies, Investment Opportunity Set, Independent Board of Commissioners, Profit Growth, And Laverage Against Profit Quality.The population in this study is a company with manufacturing types listed on the Indonesia Stock Exchange, Research period 2018-2021. The sample is taken by purposive sampling method. Data analysis using multiple linear regression. By previously testing the classical assumptions and test data normality.Â The results of this study indicate that 1) .The ownership of shares of other companies have no effect on the quality of profit. 2). Investment opportunity set affects the quality of earnings. The higher the investment opportunity the higher the accruals will be. 3). Independent Board of Commissioners affect the quality of earnings. The higher the influence of the Board of Independent Commissioners, the less the level of fraud committed by management. 4). Profit growth has no effect on earnings quality. 5). Laverage has no effect on earnings quality.